Impact of Oral Health Status on Perceived Dental Problems Among Japan Maritime Self-Defense Force Personnel. Issue 5 (29th May 2021) - Sonoda, Chikanobu; Sakurai, Yutaka; Okoda, Manabu; Ebisawa, Masato; Nakashima, Hiroshi; Tsunoda, Masashi
ABSTRACT: Introduction: Dental problems may have a great impact on military mission effectiveness, as such, evidence-based dental classification guidelines are required for minimizing the occurrence of dental problems. The aim of this study is to elucidate the independent contribution of each oral disease to the perception of dental problems among Japan Maritime Self-Defense Force (JMSDF) personnel in order to make the dental classification guidelines more precise for the prediction of future dental problems. Materials and Methods: Japan Maritime Self-Defense Force personnel who were examined during the annual dental checkup in 2013 answered questions about the experience of dental problems within the last 12 months in 2014. The associations between the items of a dental checkup and the perception of dental problems were examined using multiple logistic regression analysis with a stepwise procedure to calculate odds ratios (ORs) and 95% CIs. Results: The data of a total of 22, 441 subjects were included in the analysis. Those who declared to have perceived dental problems within the last 12 months were 5, 088 (22.7%). The multiple logistic regression analysis showed that personnel who had decayed teeth had a higher chance of experiencing dental problems than those who had no dental caries. Personnel whose periodontal disease was judged to be more severe in a dental examination had a greater OR for the perception of dental problems. Conclusion: These results may become recommendations for operations in the JMSDF dental classification system.